O afrofuturismo no romance "O céu entre mundos" de Sandra Menezes - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This dissertation investigates how Afrofuturism is manifested in the novel "O céu entre mundos" by Sandra Menezes (2021; 2024), from a perspective that centers and values the writing of Black women. By highlighting the trajectory of Sandra Menezes a Black woman and multifaceted artist engaged in literature, music, playwriting, and r epresentation the research reaffirms the transformative role of contemporary Black art in the struggle for social justice, recognition, and belonging. This study seeks to understand how the Afrofuturist narrative constructed by the author functions as a form of resistance and a means of building possible futures for historically marginalized Black people, through imagination as a tool for decolonization and the reconfiguration of Black identity in symbolic and literary fields. The investigation begins wit h the recognition of the importance of representation, the recovery of African ancestries, and the centrality of Black women’s voices in literature. In order to understand Afrofuturism a cultural and aesthetic movement that originated in the United State s and expanded globally, finding resonance in contemporary Brazilian literature this work draws on the studies of Ytasha Womack (2013; 2024), Kodwo Eshun (2015; 2020), Mark Dery (2020a; 2020b), Lisa Yaszek (2020), among others. Regarding key concepts to Afrofuturism, such as memory, identity, ancestry, and Afrocentricity, this research explores the perspectives of Leda Maria Martins (1997; 2021), Joël Candau (2011), Jeanne Marie Gagnebin (2006), Molefi Keti Asante (2016), Stuart Hall (2003; 2016), among o thers. Additionally, the discussion on women’s writing is supported by authors such as bell hooks (2015; 2017; 2019), Carla Akotirene (2019), Sueli Carneiro (2019), Teresa de Lauretis (1992), Flávia Biroli (2014), Elaine Showalter (1994), and Joan Wallach Scott (1991), in order to explore intersectionality and lived experiences. Ultimately, the analysis of the novel reveals a speculative narrative that intertwines science fiction, African ancestry, spirituality, and social critique, while promoting new hori zons for Black subjectivity and lived experience.
Afrofuturism in Sandra Menezes’ novel "O céu entre mundos"
Keywords: Afrofuturismo; Literatura negra; Interseccionalidade; Afrocentricidade; Afrofuturism; Black literature; Intersectionality; Afrocentricity; LINGUISTICA, LETRAS E ARTES::LETRAS; LETRAS::LITERATURA BRASILEIRA